HIPERBOLA DAN NARASI BENCANA ALAM: STUDI SURAH AL-ZALZALAH - Ainatus Syifa; Nabila Miftahul Husna; Hafiz Abdillah; Wati Susiawati; Mauidlotun Nisa' (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study examines the use of hyperbolic language (mubalaghah) within the linguistic structure of the Qur’an and how such stylistic devices represent natural disaster phenomena occurring in Aceh, North Sumatra, and West Sumatra, as well as their connection to the cataclysmic earthquake of the Day of Judgment as depicted in Surah Al-Zalzalah. Hyperbole functions to emphasize meaning through deliberately exaggerated rhetorical expressions that evoke emotional, spiritual, and persuasive effects on the reader. This study outlines the concept of hyperbole in the science of balaghah, the forms that appear in Surah Al-Zalzalah, and the analysis of their rhetorical functions based on both classical and contemporary tafsir. The findings show that the use of hyperbole in Surah Al-Zalzalah not only enhances the aesthetic dimension of the Qur’anic language but also presents a powerful representation of natural disasters as a theological warning about the tremendous severity of the Day of Recompense. Thus, hyperbole serves as a bridge between the literary beauty of the Qur’an and the profound conveyance of its eschatological message.